Linear relation between leaf xylem water potential and transpiration in pearl millet during soil drying - Cai, Gaochao; Ahmed, Mutez Ali; Dippold, Michaela A.; Zarebanadkouki, Mohsen; Carminati, Andrea (Plant and soil, 2020)
Aims As soil dries, the loss of soil hydraulic conductivity limits water supply to the leaves, which is expected to generate a nonlinear relationship between leaf water potential ( ψ leaf ) and transpiration ( E ). The effect of soil drying and root properties on ψ leaf and E remains elusive. Methods We measured E and ψ leaf of pearl millet for varying E and soil moisture using a root pressure chamber. A model of water flow in soil and plant was used to fit the ψ leaf ( E ) relationship. Results The relation between ψ leaf and E was linear at all soil moistures. The slope of ψ leaf ( E ) increased with decreasing soil moisture due to the decreasing soil-root conductance. The fact that the relation remained linear also in dry soils and high E is surprising. Indeed, it indicates that the gradients in soil water potential ( ψ soil ) were small, probably because of the large root surface (13.5 cm cm −3 ) active in water uptake. ψ leaf at E = 0 was less negative than ψ soil , indicating a more negative osmotic potential in the xylem than in the soil. Conclusions We propose that the linearity between ψ leaf and E and the high ψ leaf ( E = 0) compared to ψ soil support transpiration in drying soils.